The Prevalence of Modifiable Parental Behaviors Associated with Inadvertent Pediatric Medication Ingestions - Matthew Salzman; Lia Cruz; Sandra Nairn; Samuel Bechmann; Rupa Karmakar; Brigitte M. Baumann (Western Journal of Emergency Medicine, 2019)
Introduction: Our aim was to examine potential risk factors and modifiable behaviors that could lead to pediatric poisonings. Our secondary objectives were to explore socioeconomic factors associated with caregiver (parent/guardian) safe medication storage and knowledge of poison control contact information. Methods: We conducted a prospective, cross-sectional survey of caregivers of patients 2–10 years old presenting to an inner city pediatric emergency department. Caregiver and patient demographic data, prescription and nonprescription medication type, storage and when and where taken, were recorded. We used multivariable regression to explore factors associated with secure prescription medication storage and knowledge of poison control center contact information. Results: Of 1457 caregivers, 29% took daily prescription and 17% took daily non-prescription medications. Only 25% of caregivers stored their prescription medications in a secure place, and <3% stored medications in a locked drawer or safe. Of demographic and socioeconomic factors, only income ≥$80,000 was associated with storage of prescription medication in a secure place (odds ratio [OR], 2.47; 95% confidence interval [CI], 1.27–4.81). When asked how they would access poison control in case of an ingestion, the majority, 86%, had an appropriate plan. In multivariable regression, the only factor associated with knowledge of poison control center contact information was college education in the caregiver (OR 1.6; 95% CI, 1.10–2.32). Conclusion: A minority of caregivers store medications in a safe place and even fewer keep prescription medications under lock and key. The majority, however, were aware of how to contact a poison control center in case of ingestion.